Peningkatan Keterampilan Menulis Karangan Dalam Mata Pelajaran Bahasa Indonesia Melalui Penerapan Media Gambar Seri Dan Papan Cerita Bagi Siswa Kelas IV SD Negeri 3 Bawu Kemusu Tahun 2015/2016 - Wahyuni, Sri (2016)
In learning at school teachers have a major role in determining the success of learning. This study aims to: (1) Improving essay writing skills, (2) Improving learning outcomes essay writing skills. This type of research is a classroom action research. The subjects were teachers and the fourth grade students of SD Negeri 3 Bawu Kemusu the number of 21 students. Data collection techniques is done by observation, interview, test and documentation. The data analysis technique used in this study is an interactive model that includes: data presentation, data reduction and conclusion or verification. The results showed an increase in essay writing skills and essay writing skills learning outcomes through the implementation of a series of media images and storyboard for fourth grade students of SD Negeri 3 Bawu Kemusu year 2015/2016. Improved skills of essay writing as follows: (a) develop the skills aspect of the content of the essay had increased before the action that is 4 students or 19.05% after the action to 16 students or 76.19% (b) aspects form arrangement or bouquet of ways to present the content the sentence patterns have increased from the prior action that is 6 students or 28.57% after the action to 16 students or 76.19% (c) Aspects of grammar use of grammar and proper sentence patterns have increased from the prior action that is 5 students or 23 , 81% after the action to 16 students or 76.19% (d) Aspects of style options to provide structure and vocabulary of tones or colors of the bouquet has increased from before the action that is 5 students or 23.81% after the action to 18 students or 85, 71% (e) Aspects of the use of spelling and punctuation have increased from the prior action that is 8 students or 38.09% after the action to 18 students or 85.71%. Improved learning outcomes essay writing skills before action completeness of 28.57% with an average value of learning outcomes of students essay writing skills by 58.85%. After action mastery of 85.71% with an average value of learning outcomes essay writing skills of students increased again by 75.075%. From this study it can be concluded through the implementation of a series of media images and storyboard can improve essay writing skills and learning outcomes essay writing skills at the fourth grade students of SD Negeri 3 Bawu Kemusu year 2015/2016.